2004
DOI: 10.1074/jbc.m311089200
|View full text |Cite
|
Sign up to set email alerts
|

Receptor/Transporter-independent Targeting of Functional Peptides across the Plasma Membrane

Abstract: Targeting of peptides, proteins, and other functional cargo into living cells is contingent upon efficient transport across the plasma membrane barrier. We have harnessed the signal sequence hydrophobic region (SSHR) to deliver functional cargoes to cultured cells and to experimental animals. We now report evidence that two chirally distinct forms of SSHR composed of all L or all D amino acids showed similar membrane-translocating activity as assessed by confocal microscopy, flow cytometry, and direct fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…The diffusion, pore, and micelle models imply that translocation is a rapid, temperatureand energy-independent process. Consistently with these predictions substance P, R 7 W, Tat 47-57, and the signal sequence hydrophobic region peptides have been demonstrated to translocate into live cells at 4°C or in the presence of metabolic inhibitors (22,(57)(58)(59). CPP translocation across model lipid membranes also supports this notion (60,61).…”
Section: Discussionsupporting
confidence: 66%
“…The diffusion, pore, and micelle models imply that translocation is a rapid, temperatureand energy-independent process. Consistently with these predictions substance P, R 7 W, Tat 47-57, and the signal sequence hydrophobic region peptides have been demonstrated to translocate into live cells at 4°C or in the presence of metabolic inhibitors (22,(57)(58)(59). CPP translocation across model lipid membranes also supports this notion (60,61).…”
Section: Discussionsupporting
confidence: 66%
“…NLS was fused to the signal sequence hydrophobic segment from fibroblast growth factor 4. This hydrophobic segment serves as a membrane-translocating motif (MTM), which enables peptide or protein cargoes to cross freely the plasma membrane of multiple cell types in various organs (16, 20 -24) through a receptor/ transporter-independent mechanism (25). Of equal importance, these cell-permeant peptides carrying NLS have been shown to simultaneously block the nuclear import of multiple SRTFs in the cultured Jurkat T cell line, a process that is mediated by the shuttling molecule Rch1/importin ␣/karyopherin-␣ 2 (26).…”
Section: Staphylococcal Enterotoxin B (Seb)mentioning
confidence: 99%
“…Cellular import is also involved in the regulation of intracellular pathways associated with adhesion, signaling and trafficking to the nucleus. Recent studies have suggested that, in general, cell-signaling peptides translocate a functional nuclear localization sequence directly across the plasma membrane bilayers without this sequence interacting with a receptor or transporter protein in the process (5,(8)(9)(10). However, there are no high-resolution studies on the secondary structure, folding, and membrane-interaction of cell-signaling peptides to understand their transport mechanism.…”
mentioning
confidence: 99%